2009
DOI: 10.3899/jrheum.080552
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G Expression in the Skin of Patients with Systemic Sclerosis

Abstract: HLA-G is expressed in skin biopsies from patients with SSc, and this is associated with a better disease prognosis. This suggests a modulatory role of HLA-G in SSc, as observed in other skin disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
2
31
0
2
Order By: Relevance
“…Tissue HLA-G expression has been observed in the skin of patients with systemic sclerosis, who exhibited a lower frequency of vascular cutaneous lesions, telangiectasias, inflammatory polyarthritis and increased survival after a 15-year follow-up [174]. In the demyelinating disorder multiple sclerosis, levels of soluble HLA-G in the cerebrospinal fluid of patients have been inversely associated with imaging findings indicative of disease activity [175].…”
Section: Hla-g Polymorphism and Disease Associationsmentioning
confidence: 99%
“…Tissue HLA-G expression has been observed in the skin of patients with systemic sclerosis, who exhibited a lower frequency of vascular cutaneous lesions, telangiectasias, inflammatory polyarthritis and increased survival after a 15-year follow-up [174]. In the demyelinating disorder multiple sclerosis, levels of soluble HLA-G in the cerebrospinal fluid of patients have been inversely associated with imaging findings indicative of disease activity [175].…”
Section: Hla-g Polymorphism and Disease Associationsmentioning
confidence: 99%
“…In addition to the expression of HLA‐G in the dermis, in particular in mononuclear cells in the papillary dermis, whereas it was negative in normal dermis, our major finding was the striking presence of membrane‐bound and soluble forms of HLA‐G in the epidermis of affected areas and, to a lesser extent, in nonaffected skin areas of the patients. In contrast, HLA‐G expression was not observed in skin specimens obtained from healthy individuals, a finding that has been reported consistently by a number of studies 31–33 . Although the molecule has not been detected, HLA‐G mRNA has been detected in normal keratinocyte cultures and in healthy skin specimens 33,34 .…”
Section: Discussionmentioning
confidence: 75%
“…Wastowski et al. (2009) demonstrated HLA‐G expression within epidermal cells in 57% of skin biopsies from patients with systemic sclerosis 32 . HLA‐G expression was associated with more benign disease, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…First, we have demonstrated that the percentage of HLA-G positive monocytes is increased in SSc patients. Interestingly, HLA-G molecules were detected in epidermal and dermal cells of skin biopsies from approximately 50% of patients with SSc, and HLA-G expression was associated with a lower frequency of cutaneous ulcers, telangiectasias and polyarthralgias [53]. Of note, the percentage of HLA-G-positive monocytes correlated significantly with the plasma levels of sHLA-G molecules.…”
Section: Discussionmentioning
confidence: 97%